2019
DOI: 10.31557/apjcp.2019.20.2.469
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about Breast Cancer among Women in the Western Amazon: A Population-Based Study

Abstract: Objective:Evaluate the beliefs about the risk factors for breast cancer in a population of women from the western Amazon and determine the factors associated with the higher belief scores presented by this population. Methods:A population-based cross-sectional study included 478 women aged >40 years residing in Rio Branco, Acre, Brazil. An American Cancer Society questionnaire was applied to assess the knowledge, attitudes, and beliefs about breast cancer. Results:The main beliefs about the risk factors for br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Data indicate that the low offer of gynecologists is associated with higher rates of late stage detection of female breast cancer [45]. Findings of a Brazilian study have revealed that the access to gynecological assistance in the last two years and regular Papanicolaou tests lead to higher levels of information and early detection of breast cancer in Brazilian women [46]. The association between early detection and access to gynecologists can be explained by a higher adherence to breast cancer screening programs [47].…”
Section: Plos Onementioning
confidence: 99%
“…Data indicate that the low offer of gynecologists is associated with higher rates of late stage detection of female breast cancer [45]. Findings of a Brazilian study have revealed that the access to gynecological assistance in the last two years and regular Papanicolaou tests lead to higher levels of information and early detection of breast cancer in Brazilian women [46]. The association between early detection and access to gynecologists can be explained by a higher adherence to breast cancer screening programs [47].…”
Section: Plos Onementioning
confidence: 99%
“…Lack of awareness is one of the biggest barriers to BC screening and early detection [4]. This sounds alarming and we need to create more awareness about early detection, knowledge of BC symptoms and signs, and breast self-examination.…”
Section: Introductionmentioning
confidence: 99%
“…For early detection, it is important to promote breast cancer screening among the target population and quick identification of breast cancer signs and symptoms by women and/or health professionals, as well as to improve access to health services for diagnosis and treatment 5 . However, previous studies in Brazil have shown that women present limited knowledge about some breast cancer signs and symptoms 6,7 and many of them do not routinely undergo mammography screening 8 . These weak points, besides limitations in health services access, may lead women to take longer to attend a first medical visit after identifying any breast alteration suggestive of cancer.…”
Section: Introductionmentioning
confidence: 99%